2019
DOI: 10.1111/1751-7915.13423
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of central carbon metabolism in Pseudomonas aeruginosa

Abstract: SummaryMicrobes such as Pseudomonas aeruginosa are often challenged by rapidly changing nutritional environments. In order to adapt to these shifts in nutrient availability, bacteria exert tight transcriptional control over the enzymes of central metabolism. This transcriptional control is orchestrated by a series of transcriptional repressors and activators. Although a number of these transcription factors have been identified, many others remain uncharacterized. Here, we present a simple pipeline to uncover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Transcriptomic analysis of strains harboring the reproducibly occurring mutation in PP_5350 revealed that the mutation significantly activated genes responsible for the glyoxylate cycle, consistent with the deletion study 53 with P. aeruginosa (Fig. 4f).…”
Section: Validation Of Causality For the Pp_5350 Rpir Transcription Factor And Its Role In Acetate Utilizationsupporting
confidence: 78%
See 1 more Smart Citation
“…Transcriptomic analysis of strains harboring the reproducibly occurring mutation in PP_5350 revealed that the mutation significantly activated genes responsible for the glyoxylate cycle, consistent with the deletion study 53 with P. aeruginosa (Fig. 4f).…”
Section: Validation Of Causality For the Pp_5350 Rpir Transcription Factor And Its Role In Acetate Utilizationsupporting
confidence: 78%
“…PP_5350 encodes a RpiR (ribose-phosphate-isomerase regulator)-family transcriptional factor. A recent study reported that its homolog in P. aeruginosa represses the expression of aceA (encoding isocitrate lyase) and glcB (encoding malate synthase), 53 key genes in the glyoxylate cycle. 54 In addition, from a database, 55 it was found that this PP_5350 potentially interacts with genes responsible for glucose metabolism (e.g., glk encoding glucokinase, zwf encoding glucose 6-phosphate 1-dehydrogenase, eda encoding KHG/KDPG aldolase, edd encoding phosphogluconate dehydratase).…”
Section: Whole Genome Sequencing Reveals 'Key-3' Genetic Elements Related To Il Tolerancementioning
confidence: 99%
“…PA5438 is a transcriptional repressor that directly binds to the promoter region of the aceA (isocitrate lyase) gene and has been shown to repress the expression of the glcB (malate synthase) gene during growth in a non-C 2 carbon source [ 42 ]. These repressed genes encoding enzymes involved in the glyoxylate shunt (GS) pathway ( Fig 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…The pa2440 gene encodes putative polysaccharide deacetylase and it plays crucial roles in biofilm formation similar to its homologous protein BpsB in Bordetella bronchiseptica (Starkey et al ., 2009; Little et al ., 2015). h ex R (PA3184) controls glucose metabolism in response to the availability of environmental glucose through regulation of edd , glk , gltR2 and gltS gene expression (Antunes et al ., 2016; Udaondo et al ., 2018; Dolan et al ., 2020). Also, DctA encoded by PA1183 is an aerobic C4‐dicarboxylate transporter, inactivation of which resulted in growth defects in cells cultured in minimal media supplemented with succinate, fumarate or malate excluding glucose (Davies et al ., 1999; Valentini et al ., 2011).…”
Section: Resultsmentioning
confidence: 99%